(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Overactive bladder syndrome is a urinary disorder that occurs more frequently in women andolder people and is characterized by feeling an urge to urinate (sudden urge to urinate, with the feeling thatyou cannot get to the bathroom in time), doing it many times throughout the day (more than six) or havingepisodes of urinary incontinence (involuntary loss of urine) and nocturia (waking up several times duringthe night to urinate). In addition, other secondary symptoms may also occur, such as headache, dry mouth orblurred vision, among others. It is a problem that has a clear impact on the quality of life of those who sufferit and that can lead them to significantly reduce their social activity and negatively condition their work.Overactive bladder (OAB) is defined as urinary urgency with or without urgency urinary incontinence,nocturia, and/or frequency in the absence of UTI or other obvious pathology. Sacral neuromodulation is anewer surgical therapy for refractory OAB.Aim of Study: Is to assess the sacral neuromodulation (SN) safety and efficacy in refractory overactivebladder patients.Patients and Methods: In the period from November 2015 to May 2017. the unit of neurogenic bladderand neuromodulation in (Gazi Al_Harriry) surgical specialty hospital, medical city complex 27 patient agedfrom (17—55) year old were complaining from refractory overactive bladder. All the 27 patients underwentstage1 & stage2 SNS devices implantation.Results: Patients of urgency incontinence (group1) demonstrated that the number of leak was significantlyreduced (p=0.01) after implantation of SN, (11.6_2.7) leak/day pre& post SN, numbers of pads (6.9 _ 0.8)pad/day pre&post SN. Patients with urgency frequency (group 2), numbers of voids/day pre & post SNimplantation decreased significantly (p=0.01) (14.7 _ 6) voids /day. The voided volume increased significantly(p=0.02) from (136.4 _ 371.8) ml/void. The urgency episodes were decreased significantly (p=0.01) from(6.4 _ 2.1) episode/day. The complications occurred in 5 patients (18.5%). Two patients (7.4%) developedpain after trauma to the back, lead migration, lack of efficacy of device, treated by reprogramming thedevice, one patient (3.7%) get infection at the site of device implantation, SN was removed , there was onefemale patient (3.7%) got pregnancy and devise was deactivated. One patient (3.7%) complaining from painand discomfort at the device site was treated conservatively.Conclusion: Sacral neuromodulation is FDA approved as option for treatment of refractory OAB. There isexpanding of utilizing of SN in the past two decades. According to multiple studies in addition to our studyresults. The sacral neuromodulation is safe and efficacious treatment option for refractory OAB.